Está en la página 1de 7

Dierential Equations

LECTURE 25
Inverse Laplace Transforms
At the end of last class, we saw that upon using Laplace transforms on an initial value problem,
we end up with an expression for Y (s), the Laplace transform of the desired solution y(t). Thus,
we need to know how to go backwards: given a transformed function Y (s), how do we nd the
original function y(t)? This is a slightly more complicated process than taking transforms, which
was quite straightforward. We refer to f(t) as the inverse Laplace transform of F(s) and use the
notation
f(t) = L
1
{F(s)} .
Our starting point is that the inverse Laplace transform is linear, just like the original transform
was.
Theorem 25.1. Given two Laplace transforms F(s) and G(s),
L
1
{aF(s) + bG(s)} = aL
1
{F(s)} + bL
1
{G(s)}
for any constants a, b.
So, well decompose our original transformed function into pieces, inverse transform, and then
put everything back together.
This is where familiarity with the basic Laplace transforms and the table becomes handy. The
strategy is to try to identify the desired inverse transform by looking at the denominator. In most
cases, this will tell us what the original function will have to be, but occasionally we will have to
look at the numerator to distinguish between two potential inverses (e.g., the denominators for the
transforms of sin(at) and cos(at) are the same, but the numerators dier). Then, we know precisely
how we have to write our function F(s) so that it is the inverse transform of the function weve
identied as the inverse. Sometimes this requires a little bit of algebra or arithmetic.
Lets look at some examples.
Example 25.1. Find the inverse transforms of the following.
(i) F(s) =
3
s

1
s 2
+
4
s 3
This one is quite straightforward. The denominator of the rst term,
3
s
, indicates that this
will be the Laplace transform of 1. Since L{1} =
1
s
, well factor out the 3 before taking the
inverse transform. For the second term, this is just the Laplace transform of e
2t
, and theres
nothing else to do with it. The third term is also an exponential, e
3t
, and well need to factor
out the 4 in the numerator before we inverse transform.
So we have
L
1
{F(s)} = 3L
1

1
s

L
1

1
s 2

+ 4L
1
{1} s 3
f(t) = 3(1) e
2t
+ 4

e
3t

= 3 e
2t
+ 4e
3t
.
1
Dierential Equations Lecture 25: Inverse Laplace Transforms
(ii) G(s) =
5
s + 3

1
2s 4
+
7
s
3
.
The rst term is just the transform of e
3t
multiplied by 5, which well factor out before
inverse transforming.
The second term looks like it ought to be an exponential, but its got a 2s instead of an
s in the denominator, and transforms of exponentials should just have s. We can x this by
factoring a 2 out of the denominator and then taking the inverse transform.
The third term has s
3
as its denominator. This indicates that it will be related to the
transform of t
2
. The numerator isnt quite correct, though, since L

t
2

=
2!
s
2+1
=
2
s
4
. So we
would need the numerator to be 2, and right now its 7. How do we x this? Well multiply
by
2
2
, absorb the top 2 into the transform, and keep the
7
2
out front.
Lets start by rewriting the transform, with these xes incorporated.
G(s) = 5
1
s (3)

1
2(s 2)
+
2
2
7
s
3
= 5
1
s (3)

1
2
1
s 2
+
7
2
2
s
3
Now we can take the inverse transform.
g(t) = 5e
3t

1
2
e
2t
+
7
2
t
2
(iii) H(s) =
2s
s
2
+ 25
+
3
s
2
+ 16
The denominator of the rst term, s
2
+25, indicates that this should be the transform of
either sin(5t) or cos(5t). The numerator is 2s, though, which tells us that once we factor out
the 2, it will be the transform of cos(5t).
The second terms denominator is s
2
+ 16, so it will be the transform of either sin(4t)
or cos(4t). The numerator is a constant, 3, so it will be the transform of sin(4t). The only
problem is that the numerator of L{sin(4t)} should be 4, while here it is 3. Well x this, as
in the previous example, by multiplying by
4
4
.
We rewrite the transform.
H(s) = 2
s
s
2
+ (5)
2
+
4
4
3
s
2
+ 4
2
= 2
s
s
2
+ 5
2
+
3
4
4
s
2
+ 4
2
Then we take the inverse.
h(t) = 2 cos(5t) +
3
4
sin(4t).

Lets do some now that require a little more work.


Example 25.2. Find the inverse Laplace transforms for each of the following.
(i) F(s) =
3s 7
s
2
+ 16
Looking at the denominator, we recognize that this will involve a sine or a cosine, as it
has the form s
2
+ a
2
.. Its not quite either, though, since it has both an s and a constant in
the numerator, while a cosine just wants the s and the sine just wants the constant.
2
Dierential Equations Lecture 25: Inverse Laplace Transforms
This is easy to account for, however. If we split up this fraction into the dierence of two
fractions, then x them up as we did in the previous example, well be able to take our inverse
tranform.
F(s) =
3s 7
s
2
+ 16
=
3s
s
2
+ 16

7
s
2
+ 16
= 3
s
s
2
+ 16

4
4
7
s
2
+ 16
= 3
s
s
2
+ 16

7
4
4
s
2
+ 16
Now each term is in the correct form, and we can take the inverse transform.
f(t) = 3 cos(4t)
7
4
sin(4t)
(ii) G(s) =
1 3s
s
2
+ 2s + 10
If we look at our table of Laplace transforms, we might see that there are no denomina-
tors that look like a full quadratic polynomial. Also, this polynomial doesnt factor nicely.
However, there are terms in the table that have denominators of the form (s a)
2
+b
2
: those
for e
at
cos(bt) and e
at
sin(bt). We can put this denominator in that form if we complete the
square. Then we can x the numerators to gure out the inverse transform.
s
2
+ 2s + 10 = s
2
+ 2s + 1 1 + 10
= s
2
+ 2s + 1 + 9
= (s + 1)
2
+ 9
Thus, our transformed function can be written as
G(s) =
1 3s
(s + 1)
2
+ 9
.
We wont split this up into two pieces yet. First, well x the s in the numerator to be s + 1,
which well need for the numerator of e
t
cos (3t). We do this by adding and subtracting 1
to the s. This will produce some other constant term, which well combine with the already
present constant, and then we can worry about xing that numerator to correspond to the
numerator of the transform of e
t
sin(3t) .
G(s) =
1 3(s + 1 1)
(s + 1)
2
+ 9
=
1 3(s + 1) + 3
(s + 1)
2
+ 9
=
3(s + 1) + 4
(s + 1)
2
+ 9
Now we can break our transform up into two pieces, one of which will correspond to the
cosine and the other to the sine. At that point, xing the numerators is the same as in the
3
Dierential Equations Lecture 25: Inverse Laplace Transforms
last couple of examples.
G(s) = 3
s + 1
(s + 1)
2
+ 9
+
4
3
3
(s + 1)
2
+ 9
g(t) = 3e
t
cos (3t) +
4
3
e
2
sin(3t)
(iii) H(s) =
s + 2
s
2
s 12
This should appear similar at rst glance to the previous example, but theres a dierence:
this time, we can factor the denominator. This requires us to deal with the inverse transform
dierently. Factoring, we see
H(s) =
s + 2
(s + 3)(s 4)
.
We know that if we have a linear denominator, that will correspond to an exponential. In this
case, we have the product of two linear factors. This by itself isnt the denominator of any
particular Laplace transform, but we know a method for turning certain rational functions
with factored denominators into a sum of more simple rational functions with those factors
in each denominator: partial fractions.
We start by writing
H(s) =
s + 2
(s + 3)(s 4)
=
A
s + 3
+
B
s 4
.
We have to put our partial fraction decomposition over a single denominator:
s + 2
(s + 3)(s 4)
=
A(s 4) + B(s + 3)
(s + 3)(s 4)
.
This needs to be true for any value of s; in particular, the numerators must match for every
value of s:
s + 2 = A(s 4) + B(s + 3).
As a result, we can choose values of s to plug in that will isolate an individual constant. Lets
do this for each.
s = 3 : 1= 7A A=
1
7
s = 4 : 6 = 7B B=
6
7
Thus, our transform can be written as
H(s) =
1
7
s + 3
+
6
7
s 4
and taking the inverse transforms, we get
h(t) =
1
7
e
3t
+
6
7
e
4t
.

Remark. We could have done the last part of the previous example as we had the previous parts by
completing the square. However, this would have left us with expressions involving the hyperbolic
sine sinh and the hyperbolic cosine cosh. These are interesting functions which can be written in
terms of exponentials (as we got in the form of our answer to the previous example), but it will
4
Dierential Equations Lecture 25: Inverse Laplace Transforms
Factor in Denominator Partial Fractions Term
ax + b
A
ax + b
(ax + b)
k
A
1
ax + b
+
A
2
(ax + b)
2
+ . . . +
A
k
(ax + b)
k
ax
2
+ bx + c
Ax + B
ax
2
+ bx + c
(ax
2
+ bx + c)
k
A
1
x + B
1
ax
2
+ bx + c
+
A
2
x + B
2
(ax
2
+ bx + c)
2
+ . . . +
A
k
x + B
k
(ax
2
+ bx + c)
k
Table 25.1. Translation from factored denominator to partial fractions.
be much easier for us to work with the exponentials, so were better o just doing partial fractions
even though its slightly more work.
Partial fractions and completing the square are a part of life when it comes to Laplace trans-
forms. Being comfortable with these techniques is especially important when were working with
initial value problems, since most of our answers will involve some combinations of exponentials,
sines, and cosines.
Lets quickly review partial fractions. The rst step is to factor the denominator as much as you
can. Then, using Table 25.1, we can nd each of the terms for our partial fractions decomposition.
This table isnt exhaustive, but well only worry about having linear or quadratic factors.
Lets do some more examples that require partial fractions.
Example 25.3. Find the inverse transform of each of the following.
(i) F(s) =
2s + 1
(s 2)(s + 3)(s 1)
The form of the decomposition will be
G(s) =
A
s 2
+
B
s + 3
+
C
s 1
since all of the factors in our denominator are linear. Putting the right hand side over a
common denominator and setting numerators equal, we have
2s + 1 = A(s + 3)(s 1) + B(s 2)(s 1) + C(s 2)(s + 3).
We can once again use the method from the previous example where we choose key values of
s that will isolate the coecients.
s = 2 : 5 = A(5)(1) A = 1
s = 3 : 5 = B(5)(4) B =
1
4
s = 1 : 3 = C(1)(4) C =
3
4
Thus, the partial fraction decomposition for this transform is
F(s) =
1
s 2

1
4
s + 3

3
4
s 1
.
The inverse transform is then
f(t) = e
2t

1
4
e
3t

3
4
e
t
.
5
Dierential Equations Lecture 25: Inverse Laplace Transforms
(ii) G(s) =
2 3s
(s 2)(s
2
+ 3)
Now we have a quadratic in the denominator. Looking at Table 25.1, we see that the form
of the partial fractions decomposition will be
G(s) =
A
s 2
+
Bs + C
s
2
+ 3
.
If we put everything over a common denominator and setting the numerators equal, we will
get
2 3s = A(s
2
+ 3) + (Bs + C)(s 2).
Notice tht we cant use the method from the previous examples: there are only two key
values for s, but there are 3 constants, so we would be stuck at some point. Thus we need
to use the more formal method, which requires us to multiply out the right hand side and
compare coecients.
2 3s = A(s
2
+ 3) + (Bs + C)(s 2)
= As
2
+ 3A + Bs
2
2Bs + Cs 2C
= (A + B)s
2
+ (2B + C)s + (3A2C)
We have the following system of equations to solve.
(s
2
) : A + B = 0
(s
1
) : 2B + C = 3
(s
0
) : 3A2C = 2
A =
8
7
B =
8
7
C =
5
7
Thus the partial fraction decomposition is
G(s) =
8
7
s 2
+
8
7
s
s
2
+ 3

5
7
s
2
+ 3
=
8
7
1
s 2
+
8
7
s
s
2
+ 3

5
7

3
s
2
+ 3
and the inverse transform is
g(t) =
8
7
e
2t
+
8
7
cos

3t

5
7

3
sin

3t

.
(iii) H(s) =
2
s
3
(s 1)
.
The partial fraction decomposition in this case is
H(s) =
A
s
+
B
s
2
+
C
s
3
+
D
s 1
.
Setting numerators equal and multiplying out gives
2 = As
2
(s 1) + Bs(s 1) + C(s 1) + Ds
3
= As
3
As
2
+ Bs
2
Bs + Cs C + Ds
3
6
Dierential Equations Lecture 25: Inverse Laplace Transforms
and we have to solve the system of equations
(s
3
) : A + D = 0
(s
2
) : A + B = 0
(s
1
) : B + C = 0
(s
0
) : C = 2
A = 2 B = 2 C = 2 D = 2.
Thus our partial fractions decomposition becomes
H(s) =
2
s

2
s
2

2
s
3
+
2
s 1
=
2
s

2
s
2

2
2!
2!
s
3
+
2
s 1
and the inverse transform is
h(t) = 2 2t t
2
+ 2e
t
.